2019
DOI: 10.3390/su11216036
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Creative Thinking in STEM with 3D CAD Modelling

Abstract: Creative thinking is an essential part of learning for sustainability, as recent studies indicate. Creativity enables the engineer to find solutions for the design of a new product or for the improvement of one already designed, to make it more sustainable. However, currently, engineering education does not usually assess academic performance in terms of creativity, and although interest in creative processes in engineering is growing, its implementation in the classroom is still scarce. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 44 publications
(69 reference statements)
0
16
0
Order By: Relevance
“…Students' creativity and innovation are still unemployed resources in HESD [1,9]. Few studies have investigated the status quo of students' creativity within the field of SD [2,3] or their creativity skill development through HESD [4][5][6] or evaluated educational settings regarding their potential to enhance creativity in HESD [7][8][9]. However, students' innovation has so far been neglected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students' creativity and innovation are still unemployed resources in HESD [1,9]. Few studies have investigated the status quo of students' creativity within the field of SD [2,3] or their creativity skill development through HESD [4][5][6] or evaluated educational settings regarding their potential to enhance creativity in HESD [7][8][9]. However, students' innovation has so far been neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Khandakar, Chowdhury, Gonzales, Touati, Emadi, and Ayari [5] studied electrical engineering students participating in a multi-course interdisciplinary project-based learning ESD approach and found that almost all students were strongly convinced that their participation enhanced their creativity. Carbonell-Carrera, Saorin, Melian-Diaz, and Torre-Cantero [6] evaluated a creativity ESD workshop by analyzing engineering students' creative skill development with a preand post-test of performance in the individual task of solving a geometrical problem in sustainable modeling. The results indicate significant gains in the following creativity skills: abreaction, originality, figurative expansion, expressive richness, and graphic skill.…”
Section: Students' Creativity and Innovation In Education For Sustainmentioning
confidence: 99%
“…This format of educational work determines the amount of mastered content. It means that information becomes less, but the quality of its "appropriation" by the students' changes [4,15,23].…”
Section: Methodsmentioning
confidence: 99%
“…CAD 3D modeling tasks are successfully used to develop student creativity [20]. Students early familiarity with 3D CAD technology will help them better master the design skills they will need in a professional career [21].…”
Section: Content Of It Trainingmentioning
confidence: 99%